Analisis Penentuan Harga Pokok Produksi Produk Beras dengan Menggunakan Metode Full Costing pada PT. Aldi Tana Walie - Parenrengi. M; Sahade Sahade (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to find out the comparison between the determination of the cost of production of the full costing method and the method of determining the cost of production used by companies. The variable in this study is the cost of production using the full costing method. The population in this study is data on the calculation of the cost of production at PT. Aldi Tana Walie in 2022, while the sample in this study is data on the cost of raw materials, direct labor and factory overhead of PT. Aldi Tana Walie in 2022 which was taken with a purposive sampling technique. Data collection is used by observation and documentation techniques. Data analysis was carried out by qualitative data analysis using a descriptive approach. The results of the study show that there is a difference in the results of the calculation of the cost of production according to the company with the full costing method. The results of the study show that there is a difference in the results of calculating the cost of production according to the company with the full costing method. The cost of production according to the company's method which only calculates direct costs and indirect costs of IDR 366,236,000 while the calculation uses the full costing method of IDR 382,980,992. The difference in the amount of cost of production is because the company has not applied the full costing method in determining its cost of production so that the company is still not suitable in classifying production costs